ผลของการเข้าสู่ประชาคมเศรษฐกิจอาเซียนต่อการพัฒนาอุตสาหกรรมอัญมณีเละเครื่องประดับไทย - จิรารักษ์ กองแก้ว (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Thai Gems and Jewelry Industry has been ranked as one of the top worldwide manufacturing exporter from 2005-2013. Gems and Jewelry industry allows economic growth and high employment rate. In terms of the industrial development, the industry is highly rely on supporting industry and government, such as Materials , Human resources and Production technology, Along with the upcoming ASEAN Economic Community (AEC) upcoming, which will become impact on 2015,with the purpose of economic, social and culture. Based on these changing, AEC will impact directly to Thailand Gems and Jewelry Industry development. This research is aimed to examine the two relationships between Supporting Industry Government Industry Development presently. Comparison to the relationship when AEC occurs, Analyzing this relationship by Statistical Package For Social Science (SPSS) anduses a structural equation model(SEM),Finally,The changes and the level of effect that they may influence to the Thai Gems and Jewelry Industrial development. Theyalso can be used as a guideline in making stragic for Thai Gems and Jewelry Industry development toward Asean Economic Community (AEC). the view of the organization whom related to develop Thai Gems and Jewelry Industry.